Desafios regulatórios do reconhecimento facial em uma segurança pública securitizada: um olhar a partir da governança - Duarte, Hendrisy Araujo (2024)
Public security is historically a nebulous area in both politics and law. In politics, it often employs punitive discourses based on racial or social divisions. In law, there is no established right to public security, leaving gaps in legal frameworks for applying Criminal Procedure Law. The Brazilian scenario reflects the global context, worsened by a colonial legacy that persists even after the re-democratization in 1988. With society's increasing digitalization, surveillance technologies like facial recognition (FR) are being implemented without the legal system addressing the issues involved, though this has not hindered their adoption. This study aims to investigate the Brazilian State's strategies to justify the use of FR in public security. Thus, the question is raised: considering the growing use of facial recognition in Brazilian public security, how has the Brazilian State supported the use of FR from a governance perspective? The hypothetical-deductive approach is used, beginning with a general analysis of legislation and doctrines on the history of public security in Brazil and on facial recognition applied as a tool. The study presents a descending connection, addressing the perspectives of securitization of democracy and individuals, narrowing down through the analysis of governance strategies in the implementation context, considering transparency, accountability, data protection, and the guarantee of fundamental rights. The procedural methods are monographic and typological, through bibliographic and documentary research. This dissertation is divided into two chapters: the first focuses on studying the legislative history of public security and the use of technologies in this sector. Certain legal frameworks and technical aspects are examined to understand how the securitization of the state and society reshapes an exclusionary perspective, perpetuating inequalities. The "securitized" is observed as a figure of the neoliberal crisis and representative of this society, using post-democratic concepts to understand how the state has moved to implement FR in an uncritical and simplistic manner within public security. The second chapter examines the state's ambivalent role as both policy-maker in security and guardian of fundamental rights, especially considering the regulatory gap on FR and the use of governance parameters as guidelines for its implementation. It concludes that governance has been employed to reaffirm state efficiency principles, following the market logic promoted by neoliberalism. Governance should not only guide the implementation of facial recognition as a public security tool but also leverage principles of transparency, accountability, and fundamental rights protection as requirements for creating FR tools, aiming to reinforce democratic principles.